Advances in New Approach Methodologies at FDA 's Division of Applied Regulatory Science - Ksenia Blinova; Kimberly Chiu; Anik Chaturbedi; Jahan Cooper; Tromondae K. Feaster; Paula L. Hyland; Lidiya Stavitskaya; Wendy W. Wu; Jeffry Florian; Rodney Rouse (Clinical Pharmacology & Therapeutics, 2026)
New Approach Methodologies (NAMs) represent a paradigm shift in drug development and regulatory science, offering human‐relevant alternatives to traditional preclinical models. This mini‐review highlights recent advances in NAM development, validation, and regulatory application from FDA's Division of Applied Regulatory Science (DARS). We describe in silico NAMs including quantitative systems pharmacology (QSP) modeling for opioid overdose scenarios, (quantitative) structure–activity relationship ((Q)SAR) modeling for toxicity prediction and drug–drug interaction assessment, and multi‐omics approaches for pharmacodynamic biomarker discovery. Additionally, we present in vitro NAMs including human‐induced pluripotent stem cell (hiPSC)‐derived neural networks for opioid pharmacology assessment, microphysiological systems (MPS) for pulmonary drug permeability, gastrointestinal models for intestinal transport, and standardized cardiac ion channel and hiPSC‐CM MEA assays for proarrhythmia risk prediction. These case studies demonstrate how NAMs can reduce reliance on animal studies while improving translation to clinical outcomes. The NAMs described here range from exploratory research tools to approaches actively informing regulatory submissions review. The integration of in silico and in vitro NAMs into regulatory decision‐making frameworks represents a critical step toward more efficient, human‐relevant drug development and safety assessments.